2011
DOI: 10.1055/s-0030-1271028
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Mechanical and Biological Heart Valves in Dialysis and Non-Dialysis Patients

Abstract: The long-term survival of dialysis-dependent patients after AVR is low (5-year survival: 29.5 %) irrespective of the type of heart valve prosthesis. Therefore, the use of biological AVR is not contraindicated in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…After exclusion of duplicate or irrelevant references, 40 potentially relevant articles were retrieved. After application of inclusion and exclusion criteria, 16 relevant articles were included in the present systematic review and meta-analysis (7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). A total of 8,483 patients with ESRD were included for analysis, including 6,187 receiving bioprosthesis and 2,296 receiving mechanical valves.…”
Section: Literature Searchmentioning
confidence: 99%
“…After exclusion of duplicate or irrelevant references, 40 potentially relevant articles were retrieved. After application of inclusion and exclusion criteria, 16 relevant articles were included in the present systematic review and meta-analysis (7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). A total of 8,483 patients with ESRD were included for analysis, including 6,187 receiving bioprosthesis and 2,296 receiving mechanical valves.…”
Section: Literature Searchmentioning
confidence: 99%
“…A study from Germany found that 2 of 11 (18.2%) dialysis patients experienced PVE after aortic valve replacement operations compared with 71 of 2027 (3.5%) nondialysis patients (p ¼ 0.057) [11]. Another study reported that 4 of 42 (9.5%) dialysis patients who underwent valve replacement operations required reoperation for PVE [12].…”
Section: Commentmentioning
confidence: 99%
“…Another important aspect is the choice of the right prosthetic valve, which remains controversial in dialysis patients [3]. Bioprosthetic valve stenosis may be a problem in long-term care of ESRD patients.…”
Section: Commentmentioning
confidence: 99%
“…Gold standard therapy for severe AS is surgical aortic valve replacement (SAVR). In dialysis patients, SAVR is associated with increased morbidity and mortality [2,3], in particular because of a high burden of comorbidities. Data for dialysis patients suggest that transcatheter aortic valve implantation (TAVI) is feasible in this particular group [4], but that CKD including dialysis is associated with worse outcome after TAVI [5].…”
mentioning
confidence: 99%